ANALISIS KEBUTUHAN PENGEMBANGAN E-MODUL BERBASIS PROBLEM SOLVING PADA MATERI GERAK PARABOLA - Sri Purwaningsih; Azizahwati Azizahwati; Muhammad Sahal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract : The purpose of this study is to analyze the need to develop a teaching materialneeded in learning, namely e-module based problem solving on projectile motion materialfor class X SMA/MA. This study uses a qualitative descriptive method that is orientedtowards the development of a product. The subjects in this study were students of class XlSMA in the city of Pekanbaru. The data collection instrument uses a questionnaire viaGoogle Form. Then the needs analysis questionnaire filled by respondents as many as 100students, it was found that students were generally passive during the learning process.Students enjoy participating in learning that involves them actively, such as conductingexperiments. Students feel uninterested in learning if they only listen to the teacher'sexplanation, without involving their active participation. Students also feel happy if thereare learning resources that can utilize Android or IT so that the learning materials areinteractive. Then students also expect a learning process that makes them active inparticipating in learning activities. Meanwhile, for material that is considered difficult bystudents in the classroom X is parabolic motion material. The results of the needs analysisshow that it is necessary to develop problem solving based e-module teaching materialson material Projectile motion.Keywords : Needs Analysis, E-Module, Problem Solving, Projectile Motion